2014
DOI: 10.1080/15298868.2014.965732
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence That Low Social Status Is Most Toxic to Well-Being When Internalized

Abstract: What makes low social status toxic to well-being? To internalize social status is to believe the self is responsible for it. We hypothesized that the more people internalize low subjective social status, the more their basic psychological needs are thwarted. Experiment 1 randomly assigned participants to imagine themselves in low, middle, or high social status and assessed their subjective social status internalization by independent ratings. The more participants internalized low status, the more they reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 55 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…These results correspond well to the fear reactivity results, as youth of lower SSS also reported greater fear immediately after completing the task. They may be unable to regulate their fear, which is reflected in their physiology, as lower SSS has been linked with maladaptive coping previously (Jackson, Richman, LaBelle, Lempereur, & Twenge, 2015;Schubert, Süssenbach, Schäfer, & Euteneuer, 2016). They may have feared the evaluation of their performance and consequently showed a sustained reduction in RSA during recovery rather than during the preparation for the task itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results correspond well to the fear reactivity results, as youth of lower SSS also reported greater fear immediately after completing the task. They may be unable to regulate their fear, which is reflected in their physiology, as lower SSS has been linked with maladaptive coping previously (Jackson, Richman, LaBelle, Lempereur, & Twenge, 2015;Schubert, Süssenbach, Schäfer, & Euteneuer, 2016). They may have feared the evaluation of their performance and consequently showed a sustained reduction in RSA during recovery rather than during the preparation for the task itself.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the fear and parasympathetic findings, it seems that adolescents of low SSS are reacting and responding to the stress differently from those of moderate or high SSS. Lower SSS has been linked with differences in coping with stress (i.e., more depressive thinking, rumination), which may influence psychological and physiological responses to stress (Jackson et al, 2015;Schubert et al, 2016). Adolescents of lower SSS may show greater increases in fear because these youth are either more sensitive to threat or are having more difficulty regulating their affective responses to the task.…”
Section: Discussionmentioning
confidence: 99%
“…Präg et al, 2016). Being aware that one's social standing is below that of others in the social context brings about lower SSS (Jackson et al, 2015) and has been shown to have detrimental effects on health and wellbeing (Präg et al, 2014).…”
Section: Defining Subjective Social Statusmentioning
confidence: 99%
“…First, internalization of a stigmatized identity may directly impact health-related outcomes. For example, internalized homophobia (Newcomb & Mustanski, 2010), low social status (B. Jackson, Smart Richman, LaBelle, Lempereur, & Twenge, 2014), illness-related stigma (Logie, James, Tharao, & Loufty, 2013), and racism (Taylor & Jackson, 1990) have been associated either with poorer mental health, lower well-being, or health-damaging behaviors.…”
Section: Racism and Mental Healthmentioning
confidence: 99%